Magnetic susceptibility and diffuse reflectance spectroscopy to characterize the spatial variability of soil properties in a Brazilian Haplustalf - Marques, J. [UNESP]; Siqueira, D. S. [UNESP]; Camargo, L. A. [UNESP]; Teixeira, D. D. B. [UNESP]; Barron, V.; Torrent, J. (Elsevier B.V., 2014)
There is a growing demand for detailed information on soil properties. This information can be used as a guideline for sustainable production. The objective of this work was to assess the use of magnetic susceptibility (MS) and diffuse reflectance spectroscopy (DRS) for characterizing the spatial variability of soil physical and chemical properties, as well as sites with different potentials for sugarcane production, in an Haplustalf of southeastern Brazil. To this end, topsoil (0-0.20 m) and sugarcane samples were collected at the nodes of a 10 m square grid spanning an area of 1 ha. We compared the correlation between MS and DRS with the canonical pair (r = -0.26 to -034; P < 0.01) and we also compared the spatial variability models. Based on the relation between the original variables and the first canonical pair, 20% of the variance in plant properties was explained by soil attributes that did not include MS and DRS. The range values of MS (33 m) and DRS (29 to54 m) were next to those adjusted for the canonical variables of the attributes of soil (30 m) and plant (34 m). Thus, the results of this study may serve (i) to guide future work on detailed mapping in similar areas that may incorporate MS and DRS as predictive variables, and (ii) to establish the best strategy of combination of geostatistics and canonical correlation analysis for the identification of areas with different sugarcane production potential. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: Geostatistics; Canonical correlation analysis; Sugarcane; Pedometric; Detailed mapping